Insulators and domains of gene expression. (April 2016) - Ali, Tamer; Renkawitz, Rainer; Bartkuhn, Marek
Abstract : The genomic organization into active and inactive chromatin domains imposes specific requirements for having domain boundaries to prohibit interference between the opposing activities of neighbouring domains. These boundaries provide an insulator function by binding architectural proteins that mediate long-range interactions. Among these, CTCF plays a prominent role in establishing chromatin loops (between pairs of CTCF binding sites) through recruiting cohesin. CTCF-mediated long-range interactions are integral for a multitude of topological features of interphase chromatin, such as the formation of topologically associated domains, domain insulation, enhancer blocking and even enhancer function.